Heterogeneity in public health service utilization and its relationship with social integration among older adult migrants in China: a latent class analysis - Bu, Xiaolong; Wang, Ting; Dong, Qian; Liu, Cuiping (Frontiers in Public Health, 2024)
Background: The elderly migrant population in China is on the rise, which presents challenges for the national public health service system. However, the heterogeneity of public health service utilization and its relationship with social integration among the elderly migrant population remains unclear. This study aims to explore the heterogeneity the public health service utilization and how it relates to their social integration. Methods: A total of 6,178 elderly migrants from the China Migrants Dynamic Survey (CMDS) in 2017 were included in this study. Exploratory factor analysis was used to categorize social integration into four dimensions. Latent class analysis (LCA) was used to identify different sub-groups of public health service utilization. ANOVA and multivariate logistic regression were used to determine the characteristics of different sub-groups.Results: Three potential classes of public health service utilization were identified: low utilization of basic public health services class (N=3264,52.756%), medium utilization of basic public health services class(N=1743,28.172%), and high utilization of basic public health services class (N=1180,19.072%). Gender, education, extent of mobility, and move alone or not , flow time were all predictors of the class of public health service utilization. There were significant differences in social integration across potential categories(p＜0.0001) Conclusions: The utilization of public health services of the elderly migrants is affected by many aspects. Social integration deserves attention as a significant influencing factor in the utilization of public health services. The government should pay attention to the characteristics of the elderly migrants and formulate relevant policies in a targeted manner in order to improve the utilization of public health services of the elderly migrants.